Medicinal Plants and Natural Substances for Poultry Health: A Review - Pashaei, Mohsen; Fayçal, Zeroual; Kahrizi, Danial; Ercisli, Sezai (Journal of Poultry Sciences and Avian Diseases, 2024)
The global poultry industry relies heavily on antibiotics to prevent and treat diseases and promote growth. However, the rise of antibiotic-resistant bacteria poses significant risks to both animal and human health, necessitating alternative approaches to maintain health and productivity. This review systematically examines the evidence for medicinal plants and their bioactive components as non-antibiotic interventions and growth promoters in poultry species. Numerous herbs, spices, plant extracts, essential oils, and isolated phytochemicals demonstrate beneficial bioactivities relevant to poultry production in vitro and in vivo, including antimicrobial, anti-inflammatory, immunomodulatory, and antioxidant effects. While considerable research confirms positive impacts on performance under experimental conditions, questions remain regarding bioavailability, mechanisms, efficacy, safety, feasibility, and suitability for commercial integration that currently impede widespread adoption as antibiotic alternatives. Further high-quality controlled trials directly analyzing physiological responses, production impacts, safety profiles, and cost-effectiveness analysis are warranted to support the integration of evidence-based phytogenic feed additives in poultry production systems.